Exposure of Mental Health Nurses to Violence in Mental Hospital : a Systematic Review - Iyus Yosep; Zabidah Putit; Helmy Hazmi; Henny Suzana Mediani (Jurnal Keperawatan Padjadjaran, 2016)
Shortage of nurses and declining interest in becoming a mental health nurse are often attributed to workplacedistress and violence. These have become global issues and believed that shortage of nurses decreases the qualityof health care services. It leads distress among nurses, which is exposure to violence and traumatic experiences.In addition, nurses are also accused of seizing the rights of patients and committing violence against a patient.This paper focuses on the violence that occurred in mental health nurses during working in unpredictablesituation. A literature search of systematic review through the CINAHL, Medline, Google scholars and PsycInfodatabases, the empirical report using a nursing sample includes data on rates of violence exposure includingviolence, aggressive behavior, bullying, and sexual harassment. The result, a total of 400 articles provide dataon 2742 publications indicates near all of nurses in mental health experienced verbal abuse in the past month,furthermore, most of respondents’ ever experienced psychological abuse, and less of respondents experiencedphysical violence and sexual harassment. Rates of exposure vary by world region (Developed countries, Asia,Europe and Middle East), with the highest rates for physical violence and sexual harassment in the USA,Australia, United Kingdom, New Zealand region, and the highest rates of psychological violence and bullyingin the Middle East. The presence of violence signals an "alarm" that violence against nurses calls for specialattention in many countries. Essentially, the world must give a "priority" to handling violence against nurses.